The exon A (C77G) mutation is a common cause of abnormal CD45 splicing in humans. - Tchilian, E; Wallace, D; Imami, N; Liao, H; Burton, C; Gotch, F; Martinson, J; Haynes, B; Beverley, P (2001)
The leukocyte common (CD45) Ag is essential for normal T lymphocyte function and alternative splicing at the N terminus of the gene is associated with changes in T cell maturation and differentiation. Recently, a statistically significant association was reported in a large series of human thymus samples between phenotypically abnormal CD45 splicing and the presence of the CC chemokine receptor 5 deletion 32 (CCR5del32) allele, which confers resistance to HIV infection in homozygotes. We show here that abnormal splicing in these thymus samples is associated with the presence of the only established cause of CD45 abnormal splicing, a C77G transversion in exon A. In addition we have examined 227 DNA samples from peripheral blood of healthy donors and find no association between the exon A (C77G) and CCR5del32 mutations. Among 135 PBMC samples, tested by flow cytometric analysis, all those exhibiting abnormal splicing of CD45 also showed the exon A C77G transversion. We conclude that the exon A (C77G) mutation is a common cause of abnormal CD45 splicing and that further disease association studies of this mutation are warranted.